Michael Arlen’s The Green Hat: Reassessing the Impact a Hundred Years Later - Lusine Kh. Hambardzumyan Mueller (Литература двух Америк, 2025)
In 1924, Michael Arlen published his novel The Green Hat and catapulted to immediate notoriety, even becoming Time’s “Man of the Year.” One hundred years later, the name Michael Arlen is barely recognized. This article reexamines The Green Hat on the occasion of its 100th anniversary of publication. Through a study of the real-life connections of The Green Hat to Arlen’s relationship with Nancy Cunard and an examination of contemporary literary reviews, this analysis traces the ways in which other famous writers of the Jazz Age, including Ernest Hemingway, F. Scott Fitzgerald, and Aldous Huxley, appropriated Arlen’s motifs and his main character Iris Storm. It also examines the bias against Armenians in England in the 1920s and 1930s, which this author argues contributed to the minimization of Arlen’s true impact. This article contends that, far from being the discounted or disparaged figure that critics portray him to be, Arlen should hold a much more pivotal place in the canon of the Jazz Age.